Rationales for Internationalisation of Higer Education - Wit, Hans de (2011)
Internationalisation is high on the agendas of national governments, international bodies and institutions of higher education. European programmes like SOCRATES and international networks of universities, are just two examples of the way in which the international dimension has captured higher education in the past fifteen years. Are we at the beginning of a future in which we are, in the words of Clark Kerr (1994, 9), on our way again to the "universalism of learning: the universal-university world", the revival of the cosmopolitan university of the medieval times, but within the context of a new modern world and a new age, the information age, in which society, economy and knowledge are part of a global environment, a mix of local and global influences?